La condición femenina: influencia en el desarrollo de la enfermería y en el desarrollo humano de las (los) profesionales (2002)
ABSTRACT: The article intents to make about the social constructions on the feminine and its effects on women’s life, through a paradigmatic case as the nursing profession. The first instance analyzes the meaning of cultural constructions of the feminine in women’s life, second, discusses the relations between the nursing profession, feminine condition and influence on human development, and third, presents some alternatives changes to better the problems exposed.